Financial Optimization for MSMEs through Receivables and Financial Reporting Training at Djack Auto Car - Stepani Sisca Wulandari; Akbar, Taufiq; Edy Sukarno; Salsabila Ramadini; Yumeizy Syahputra (Edumedia Solution, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia’s economy but often struggle with financial management, including ineffective receivables recording, limited digital system usage, and basic financial reporting. This community service program aimed to strengthen the managerial and financial capacity of Djack Auto Car, a microenterprise in the automotive service sector, through training, system implementation guidance, and continuous evaluation. Key interventions included soft collection strategies, structured financial recording, and basic taxation, supported by practical modules, templates, and dashboards. Pre-test results showed limited knowledge, with average scores of 57.1 for soft collection and 60 for financial and taxation topics. Post-test results demonstrated substantial improvement, increasing to 82.1 and 83.2, respectively. Field observations indicated that the partner began applying systematic receivables management, conducting timely collections, preparing periodic financial reports, and practicing prudent credit risk management. The program enhanced operational efficiency, data-driven decision-making, and awareness of proper business reporting and tax obligations. Recommendations include sustaining and optimizing the implemented systems, conducting regular financial monitoring, offering advanced financial tools training, and fostering business networks to support long-term, sustainable growth.